2020
DOI: 10.1111/jcmm.15571
|View full text |Cite
|
Sign up to set email alerts
|

β‐Methylphenylalanine exerts neuroprotective effects in a Parkinson's disease model by protecting against tyrosine hydroxylase depletion

Abstract: We evaluated the neuroprotective effects of β‐methylphenylalanine in an experimental model of rotenone‐induced Parkinson's disease (PD) in SH‐SY5Y cells and rats. Cells were pre‐treated with rotenone (2.5 µg/mL) for 24 hours followed by β‐methylphenylalanine (1, 10 and 100 mg/L) for 72 hours. Cell viability, reactive oxygen species (ROS) levels, mitochondrial membrane potential (MMP), mitochondrial fragmentation, apoptosis, and mRNA and protein levels of tyrosine hydroxylase were determined. In a rat model of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Past research found that octanoylcarnitine and decanoylcarnitine were closely correlated with the treatment effect of ESCC (26). (2S,3S)-3-Methylphenylalanine can prevent mitochondrial damage and reduce apoptosis of cells (40). The level of 3-(pyrazol-1-yl)-L-alanine is closely related to gastric cancers (41).…”
Section: Discussionmentioning
confidence: 96%
“…Past research found that octanoylcarnitine and decanoylcarnitine were closely correlated with the treatment effect of ESCC (26). (2S,3S)-3-Methylphenylalanine can prevent mitochondrial damage and reduce apoptosis of cells (40). The level of 3-(pyrazol-1-yl)-L-alanine is closely related to gastric cancers (41).…”
Section: Discussionmentioning
confidence: 96%
“…In the retina, dopamine is synthesized by subtype A18 cells without long protrusions or cells of the inner plexiform layer (Lin 2011), which are mainly found in the inner plexiform and inner nuclear layers of the retina (Jackson, et al 2014) and can affect the activity of a variety of cells within the retina (Lin 2011). TH is the rate-limiting enzyme for dopamine synthesis, and its level is indicative of dopamine levels (Feng, et al 2020). This study found that the TH uorescence intensity in the inner plexiform and inner nuclear layers of the left retina (contralateral to the lesion) was reduced by more than 80% and 90%, respectively, in the PD group compared with the control group at 14 and 28 days after lesioning and that the TH uorescence intensity in bilateral retina increased signi cantly after magnesium sulfate supplementation, suggesting that the loss of retinal dopaminergic neurons in PD rats increased with the progression of PD.…”
Section: Discussionmentioning
confidence: 99%